2018
DOI: 10.1096/fj.201800247r
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance of vector beetle to its partner plant parasitic nematode modulated by its insect parasitic nematode

Abstract: Immune response of insect vectors to transmitted pathogens or insect hosts against parasites are well studied, whereas the mechanism of tripartite interactions remains elusive. In this study, we investigated the immune interactions of the vector beetle Monochamus alternatus ( Ma) to the devastating plant parasitic nematode Bursaphelenchus xylophilus ( Bx) and the insect parasitic nematode Howardula phyllotretae ( Hp). We report the unique immune mechanism by which the vector beetle tolerates many devastating B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Some previous studies have already shown that the expression of several genes in M. alternatus was altered when infected by B. xylophilus . For example, Zhou et al [ 31 ] showed that in order to obtain immune tolerance, M. alternatus infected with B. xylophilus would induce an increase in the expression of antioxidant genes. Through the increased expression of these antioxidant genes, the level of ROS in the trachea of longicorn beetles increases and reaches a state of equilibrium [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some previous studies have already shown that the expression of several genes in M. alternatus was altered when infected by B. xylophilus . For example, Zhou et al [ 31 ] showed that in order to obtain immune tolerance, M. alternatus infected with B. xylophilus would induce an increase in the expression of antioxidant genes. Through the increased expression of these antioxidant genes, the level of ROS in the trachea of longicorn beetles increases and reaches a state of equilibrium [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhou et al [ 31 ] showed that in order to obtain immune tolerance, M. alternatus infected with B. xylophilus would induce an increase in the expression of antioxidant genes. Through the increased expression of these antioxidant genes, the level of ROS in the trachea of longicorn beetles increases and reaches a state of equilibrium [ 31 ]. Coincidentally, as one of the main sources of ROS, the genes ND4 and ND5 , which code for two subunits of Complex I, were found to be significantly up-regulated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nematodes inhabit a diversity of habitats and can be free‐living ( Caenorhabditis elegans and C. briggsae ), animal‐parasitic ( Strongyloides stercoralis in mammals, Brugia malayi and Enterobius vermicularis in humans) and plant‐parasitic ( Meloidogyne incognita and M. hapla in many crops and Globodera pallida in potatoes among others) (Coghlan, ). Consequently, nematodes experience a much greater array of deleterious xenobiotic exposure in soils (Lindblom & Dodd, ) and insect haemolymph (Zhou et al, ) and to plant defence chemicals (Niu, Zhao, Lu, Zhang, & Sun, ). Thus, xenobiotic detoxification is necessary for survival.…”
Section: Introductionmentioning
confidence: 99%